The Influence of Work Discipline and Physical Work Environment on Employee Performance at CV X, Sidoarjo - Erie Aulia; Kustini Kustini (International Journal of Economics and Management Sciences, 2025)
The purpose of this study is to analyze the extent to which work discipline and the physical work environment influence employee performance at CV X. The research was conducted using a quantitative approach involving all 45 production employees, with a saturation sampling method to ensure that every member of the population was represented. Data were collected through a structured questionnaire using a five-point Likert scale, while hypothesis testing was carried out using the SEM-PLS method to obtain more accurate estimates of the relationships among variables. The results reveal that both work discipline and the physical workplace contribute significantly to performance improvement. The physical work environment shows a positive and meaningful effect on employee performance, as indicated by a path coefficient of 0.464, a T-statistic of 2.309, and a P-value of 0.002. Similarly, work discipline also demonstrates a constructive influence, supported by a path coefficient of 0.403, a T-statistic of 2.786, and a P-value of 0.006. Based on the R-square value of 0.701, the two variables collectively explain 70.1% of the variance in employee performance. These findings highlight the importance of fostering disciplined work behavior while simultaneously enhancing environmental conditions in the workplace. Improving the physical layout, comfort, and safety, along with reinforcing consistent adherence to organizational rules, can substantially elevate performance outcomes at CV X.